MACROECONOMIC FACTORS AND THEIR INFLUENCES ON FINANCIAL PERFORMANCE IN INDONESIAN LOCAL GOVERNMENTS - Kuntaryanto, Oki (Kiat Bisnis, 2012)
AbstractÂ The use of financial ratios to measure financial performance is a common practice in private sector. However, this research uses those ratios and applies them in public sector. Financial performance is represented by financial ratios comprising profitability ratios, short-term solvency ratio, capital structure ratios and performance ratios. The conjectured factors, which influence financial performance, are macroeconomic factors represented by GRDP and inflation. This research tries to extend a model developed by Kuntaryanto (2012) by adding other financial ratios. Thus, this research does not only incorporate profitability ratio but also other ratios; short-term solvency, capital structure, and performance ratios. The financial reports included in data analysis are those, which do not have adverse and disclaimer opinions. Ordinary least squares regression technique is employed for testing the hypothesis for cross-sectional data. In addition, panel analysis is employed to test the time change effect. This research finds that macroeconomic factors have influences on financial performance. Thus, the finding does not only generalize the previous research as conducted by Kuntaryanto (2012), but also finds several variables that have influence on financial performance.Keywords:Â Financial performance, Financial ratios, Local governments, Indonesia, Macroeconomic factors